Small Cell Lung Cancer Transformation as a Resistance Mechanism to Osimertinib in Epidermal Growth Factor Receptor-Mutated Lung Adenocarcinoma: Case Report and Literature Review - Leonetti, Alessandro; Minari, Roberta; Mazzaschi, Giulia; Gnetti, Letizia; La Monica, Silvia; Alfieri, Roberta; Campanini, Nicoletta; Verzè, Michela; Olivani, Andrea; Ventura, Luigi; Tiseo, Marcello (Frontiers in Oncology, 2021)
Introduction: Small-cell lung cancer (SCLC) transformation represents a mechanism of resistance to osimertinib in EGFR-mutated lung adenocarcinoma, which dramatically impact patients’ prognosis due to the high refractoriness to conventional treatments. Case description: We present the case of a patient who developed a SCLC phenotypic transformation as resistance mechanism to second-line osimertinib for T790M-positive EGFR-mutated NSCLC. Our patient received platinum-etoposide doublet following SCLC switch and achieved a modest clinical benefit which lasted four months. NGS and IHC analyses for p53 and Rb were performed on subsequent liver biopsies, revealing baseline TP53 mutation and complete absence of p53 and Rb expression. Primary cell cultures were established following a liver biopsy at the time of SCLC transformation and drug sensitivity assays showed a meaningful cell growth inhibition when osimertinib was added to platinum-etoposide compared to control (p<0.05). A review of the current literature regarding SCLC transformation after failure of osimertinib was performed. Conclusions: Based on retrospective data available to date, platinum-etoposide chemotherapy is the preferred treatment choice in the occurrence of SCLC transformation after osimertinib failure. The extension of osimertinib in combination with chemotherapy in the occurrence of SCLC transformation as resistance mechanism to osimertinib is a matter of debate. The combination of osimertinib and platinum-etoposide was effective in inhibiting cell growth in our primary cell cultures. Clinical studies are needed to further explore this combination in the occurrence of SCLC transformation as a resistance mechanism to osimertinib.